Pemanfaatan Alat Evaluasi Untuk Meningkatkan Hasil Belajar Pada Materi APBN & APBD Siswa Kelas XI IPA - Shafa Rizqi Nabilah; Waspodo Tjipto Subroto (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2021)
The purpose of this study is to analyze the differences in learning outcomes and to analyze the effectiveness of the use of evaluation tools on learning outcomes in State Expenditure Revenue Budget and Regional Expenditure Budget materials toward student in science class XI. The experiment research and nonequivalent control group design is used, with a population of 170 students with majors in Science. In selecting the sample, researcher uses purposive sampling technique with Science class XI 3 as the experimental class and Science class XI 4 as the control class, But the only difference in the experimental class is given as additional evaluation tools. This study uses hypothetical test of pre-test value and post-test with One Way Anova. Based on these results, in the use of evaluation tools there was no significant difference in student learning outcomes in State Expenditure Revenue Budget and Regional Expenditure Budget materials toward student ins science class XI and the use of evaluation tools had effectiveness as a support for improving learning outcomes with State Expenditure Revenue Budget and Regional Expenditure Budget materials toward student ins science class XI.DOI: https://dx.doi.org/10.17977/UM014v14i22021p116